Student Views of Teacher Actions in Science Classrooms Designed to Meet Current Reforms - DOĞAN, ÖZGÜR KIVILCAN (SPRINGER, 2013)
Science/Technology/Society (STS) as a reform effort has been active in Iowa for three decades. A program called Iowa Chautauqua has evolved over the four decades to promote K-12 STS teaching in Iowa's 300 school districts. This is a study of how teachers have become Teacher Leaders of the reforms and lead other teachers who enroll as new teachers and schools each New Year. All were involved with Action Research projects each year while also assisting graduate student teams who serve as research associates. In this study, students were asked to identify specific teacher actions that were designed to make student learning more successful. The study examines general student views of teacher actions as well as specific examples of how students interact with the teacher and how the teachers encourage greater student/student involvement. The results show success with STS and how it defines science and affective actions of teachers in classrooms. Student views of Teacher Leaders, new Chautauqua teachers, and Control Teachers with no STS or Chautauqua experiences provide ways of recognizing successes of current reform efforts.
Keywords: STS; Chautauqua; Current reforms